Optimizing the capture of neophobic rice field rats in lowland Asian rice ecosystems - Lorica, Renee P.; Stuart, Alexander M.; Singleton, Grant R.; Sudarmaji; Belmain, Steven R. (Wiley, 2022)
Trapping is a key method for monitoring small mammals and is also one of a number of methods recommended under an ecologically‐based rodent management program to control rodent pest populations. Live‐traps are widely used globally for studying small mammal populations. In Asia where rodents are major pests of rice, single capture traps typically provide low trap success. We compared the trap success between two types of live‐traps in rice fields in Indonesia and the Philippines.RESULTSMultiple‐capture traps (MCTs) in conjunction with a linear trap barrier were significantly more effective in catching rodent pest species than single‐capture traps (SCTs) in Indonesia and the Philippines. In Indonesia, MCTs captured more individuals with a mean (±SE) percent trap success rate of (15.54 ± 4.29) compared to SCTs (3.88 ± 1.58). In the Philippines, MCTs captured more species of rodents and had a significantly higher recapture rate (1.96 ± 0.79), than SCTs (0.58 ± 0.32).CONCLUSIONMultiple‐capture traps with a linear trap‐barrier were more effective for capturing Rattus argentiventer and Rattus tanezumi in rice field ecosystems compared to single‐capture traps. MCTs captured more species of rodent pests in the Philippines and recaptured more individuals of each species. These results indicate that rodent populations can be more effectively monitored and controlled by using a multi‐capture trap with barrier system than the use of single capture traps on their own. This is the first time these two trap types have been compared for use in rice ecosystems in Asia. © 2022 The Authors. Pest Management Science published by John Wiley and Sons Ltd on behalf of Society of Chemical Industry.